Low‐density lipoprotein cholesterol : high‐density lipoprotein cholesterol ratio is associated with incident diabetes in Chinese adults: A retrospective cohort study - Wei, Limin (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: Dyslipidemia plays a critical role in the pathogenesis of metabolic syndrome and diabetes. Evidence has increasingly shown that the ratio of low‐ to high‐density lipoprotein cholesterol (LDL‐C/HDL‐C) is a novel marker for increased risk of insulin resistance and cardiovascular diseases. However, the correlation between the LDL‐C/HDL‐C ratio and diabetes risk is rarely reported. This is the first study to investigate the association between the LDL‐C/HDL‐C ratio and new‐onset diabetes in a large community‐based cohort. MATERIALS AND METHODS: In this retrospective cohort study, a total of 116,661 adults without baseline diabetes were enrolled. Participants were stratified into four groups based on LDL‐C/HDL‐C ratio quartiles. The outcome of interest was new‐onset diabetes. RESULTS: During a median follow‐up period of 2.98 years, 2,681 (2.3%) new diabetes cases were recorded. The total cumulative incidence of diabetes progressively increased alongside LDL‐C/HDL‐C ratio quartiles (0.31, 0.43, 0.68 and 0.88%, respectively, P‐value for trend <0.001). After adjusting for potential confounders, using the lowest quartile of the LDL‐C/HDL‐C ratio as the reference, the risk of diabetes increased with LDL‐C/HDL‐C ratio quartiles (P‐value for trend <0.001); in particular, from the second to fourth quartile, hazard ratios were 1.18 (95% confidence interval 0.87–1.59), 1.42 (95% confidence interval 1.07–1.90) and 1.92 (95% confidence interval 1.43–2.59), respectively. The results were also robust to challenges in multiple sensitivity analyses. CONCLUSIONS: Among the Chinese population, elevated LDL‐C/HDL‐C ratio might be an independent risk factor for new‐onset diabetes.